2010
DOI: 10.1590/s1516-18462010005000119
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do processamento auditivo das crianças com distúrbio de leitura e escrita de 8 a 12 anos em tratamento no Centro Clínico de Fonoaudiologia da Pontifícia Universidade Católica de Minas Gerais

Abstract: RESUMOResultados: verificou-se que todos os indivíduos apresentaram alterações em pelo menos uma habilidade auditiva do processamento auditivo.Conclusão: Verificou-se estreita e estrita relação entre as habilidades do processamento auditivo e o distúrbio de leitura e escrita. Os procedimentos que se destacaram na identificação de anormalidades no processamento neurológico da informação auditiva foram os testes SSW, PSI com palavras no ruído e Teste de Padrão de Freqüência melódico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 21 publications
1
21
1
7
Order By: Relevance
“…These results corroborate the findings of other studies that indicate similar results, explaining that boys have more language and learning disorders than girls 1,8,17 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results corroborate the findings of other studies that indicate similar results, explaining that boys have more language and learning disorders than girls 1,8,17 .…”
Section: Discussionsupporting
confidence: 92%
“…Alterations in auditory processing can occur alone or be found in association with other learning disorder comorbidities as demonstrated in other studies 1,[8][9][10][11][12] . In this sense, early detection is essential to the minimization of the linguistic, cognitive and psychosocial impact of APD, as well as to organize appropriate speech rehabilitation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A study developed with 18 subjects of similar age, of which eight had temporal lobe epilepsy and ten without cortical damage, it was observed that individuals with epilepsy had more deficits in auditory Figure 1 presents the publications [25][26][27][28][29][30][31][32][33][34][35] It was observed that, in most studies of individuals who had speech pathology, the temporal ordering ability was impaired, and FPT was the test most frequently used to assess this ability.…”
Section: Clinical Applications Of Frequency Patterns and Duration Patmentioning
confidence: 99%